Asymptotic behavior of orthogonal polynomials corresponding to a measure with infinite discrete part off an arc - R. Khaldi; R. Benzine (International Journal of Mathematics and Mathematical Sciences)
We study the asymptotic behavior of orthogonal polynomials. The measure is concentrated on a complex rectifiable arc and has an infinity of masses in the region exterior to the arc.